Morphological Process of Morphemes Through Word-Formation Process in Students’ Writing - Moh Shofi Zuhri; Suwandi Suwandi; Sri Wuli Fitriati (English Education Journal, 2022)
In learning a language, students must learn about linguistics and its branches to know the context of language, the origin of words and how they are formed. This study aimed to investigate word-formation by exposing Yule’s (2010) theory in students’ writing. This research focused on how many word-formations existed and how the word-formation process was applied in students’ writing. A descriptive qualitative approach was adopted to analyze the gathered data to fulfill the research objectives. The data were collected through observation. The participants in this research were 18 students of Universitas Negeri Semarang attending Academic Writing class. The findings show that the students applied 599 processes which fall under five types of word-formations. They could be categorized into blending, compounding, clipping, derivation, and inflection. The students applied less blending and clipping word-formation processes. In addition, there were some problems in applying the word-formation process. Some students were confused about how to form blending and clipping. Hopefully, this research will give significant contribution as reference in understanding word formation. The present study is expected to contribute to teaching and learning of word-based lexical studies in general and word-formations in particular.